Застосування ультразвуку при катетеризації внутрішньої яремної вени у пацієнтів з ожирінням - Воротинцев, Сергій Іванович; Софілканич, Михайло Михайлович; Захарчук, Олександр Валентинович; Воротынцев, С. И.; Софилканич, М. М.; Захарчук, А. В; Vorotyntsev, S. І.; Sofilkanych, M. M.; Zakharchuk, O. V. (My University, 2018)
Ускладнення катетеризації внутрішньої яремної вени (VJI) у пацієнтів з ожирінням в основному пов’язані з важкістю її пункції на основі анатомічних орієнтирів. Використання ультразвуку (УЗ) для цієї процедури має гарні показники якості та безпеки в загальній популяції пацієнтів. В дослідженні була оцінена ефективність УЗ-підтримки при катетеризації VJI, в порівнянні з «сліпою» технікою, у 40 пацієнтів з ожирінням. Виявлено, що при застосуванні УЗ середній час доступу та кількість спроб були вдвічі нижчими, ніж без нього (27,1±26,5 сек проти 54±99,4 сек та 1,1±0,6 разів проти 2,6±2,9 разів відповідно, p<0,05), успішність катетеризації склала 100% (p<0,05), та не було зафіксовано жодного механічного ускладнення катетеризації (p<0,05). Таким чином, катетеризація VJI під контролем ультразвуку у пацієнтів з ожирінням, в порівнянні з технікою на основі анатомічних орієнтирів, має переваги у вигляді скорочення часу та зменшення кількості спроб для виконання процедури, що, безперечно, підвищує успішність катетеризації до максимального рівня (100%) та зменшує кількість механічних ускладнень до мінімального рівня (0%). Осложнения катетеризации внутренней яремной вены (VJI) у пациентов с ожирением в основном связаны со сложностями ее пункции на основе анатомических ориентиров. Использование ультразвука (УЗ) для этой процедуры имеет хорошие показатели качества и безопасности в общей популяции пациентов. В исследовании была оценена эффективность УЗ-поддержки при катетеризации VJI, в сравнении с «слепой» техникой, у 40 пациентов с ожирением. Выявлено, что при применении УЗ среднее время доступа и количество попыток были вдвое меньшими, чем без него (27,1±26,5 сек против 54±99,4 сек и 1,1±0,6 раз против 2,6±2,9 раз соответственно, p<0,05), успешность катетеризации составила 100% (p<0,05), и не было зафиксировано ни одного механического осложнения катетеризации (p<0,05). Таким образом, катетеризация VJI под контролем ультразвука у пациентов с ожирением, в сравнении с техникой на основе анатомических ориентиров, имеет преимущества в виде сокращения времени и уменьшения количества попыток для выполнения процедуры, что, безусловно, повышает успешность катетеризации до максимального уровня (100%) и уменьшает количество механических осложнений до минимального уровня (0%). Among possible complications of central veins catheterization in obese patients there can be problems associated directly with venous puncture, the need to evaluate intravenous length of the catheter and confirmation of the catheter tip placement in the vein. Some authors recommend using ultrasound (US) for catheterization of internal jugular vein (VJI) in bariatric patients as a first-choice technique that has good quality and safety indicators. However, in no one of the current recommendations and meta-analysis for central venous catheterization the subgroup of patients with obesity is singled out. The aim of our work was to evaluate the effectiveness of US support during VJI catheterization in obese patients. In a single-center, prospective randomized study there were consistently included 40 patients with a body mass index (BMI) >30 kg/m2 to whom VJI catheterization was prescribed. Patients were divided into two groups: group A, where VJI catheterization was carried out by an experienced anesthesiologist based on anatomical landmarks (n=20), and group B, where the VJI catheterization was performed by an experienced US-interventionist with the use of ultrasound control in real time with the help of 12L-RS linear probe (7-12 MHz) and Logiq e (GE, USA) (n=20). Successful placement of the catheter was determined by the free flow of blood in it. To compare catheterization techniques the following endpoints were selected: the time of access (time between skin puncture and venous blood aspiration in a syringe via VJI catheter), number of attempts before successful placement of the catheter (defined as individual punctures of the skin), catheterization success, number of mechanical complications (carotid puncture, hypodermic hematoma, pneumothorax, haemothorax, incorrect placement of the catheter). Statistical analysis was provided with a program Statistica for Windows version 6.0. It was found that in group B the average access time and the number of attempts were twice lower than in the group A (27.1±26.5 sec vs 54±99.4 sec and 1.1±0.6 times vs 2.6±2.9 times accordingly, p<0.05). The rate of catheterization success in group B was 100% and in group A – 80% (p<0.05). At the same time there was no mechanical complication in group B. Three cases of puncture of the common carotid artery with the development of significant subcutaneous haematoma were observed in group A (p<0.05), but neither pneumothorax nor haemothorax were observed. Five essential anatomical varieties between the VJI and the common carotid artery were observed in group B. In 8 cases (40%) VJI was placed ahead and laterally from the artery, in 5 cases (25%) VJI had absolutely lateral position, in 3 (15%) cases VJI was directly above the common carotid artery. In 3 (15%) patients VJI was in the front and medially from the common carotid artery and in 1 (5%) of patients VJI – even medially from the artery. So, we found that VJI catheterization under ultrasound control in obese patients in comparison with the technique based on anatomical landmarks has advantages in time reduction and reducing the number of attempts to perform the procedure, which undoubtedly increases the catheterization success to the maximum level (100%) and decreases the number of mechanical complications to the minimum level (0%).
Применение ультразвука при катетеризации внутренней яремной вены у пациентов с ожирением
The use of ultrasound during catheterization of internal jugular vein in patients with obesity
Keywords: ожиріння; катетеризація внутрішньої яремної вени; ультразвук; ожирение; катетеризация внутренней яремной вены; obesity; catheterization of internal jugular vein; ultrasound